Occurrence of deviated nasal septum in terms of angles and its relation with sinus disease in patients of chronic rhinosinusitis: a computed tomography scan study - Sonone, Jayant K.; Garg, Deepika; Solanke, Poonam S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The intention of this study was to evaluate angles of nasal septal deviation by measuring angle of nasal septal deviation on computerized tomography of the para nasal sinuses (CT PNS) and to study the effect of increasing septal angle on chronic sinusitis. No other study in the literature has measured exact angle of septal deviation in terms of degrees. Methods: A prospective cross-sectional observational study was carried out from September 2015 to August 2017 and 57 patients with diagnosis of having chronic sinusitis, were evaluated with CT PNS (coronal and axial views). Results: Most patients of chronic rhinosinusitis had septal deviation in grade III, followed by grade II, then grade I. Conclusions: This study concludes that higher the angle of septal deviation, higher the incidence of CRS and vice versa.